Research into the structural-mechanical properties of shortbread dough with oilseed meals - Kravchenko, Mihailo; Mihailik, Vitalii; Yakymchuk, Dmytro; Dzyundzya, Oksana; Burak, Valentyna; Romanenko, Olena; Valko, Mykola; Korolenko, Evgenia; Osypenkova, Iryna; Bondarchuk, Zoia (Eastern-European Journal of Enterprise Technologies, 2019)
This paper reports results of research into the application of oil-seed meal in the technology of flour-based confectionery products, specifically shortbread dough. We have investigated the structural-mechanical properties of shortbread dough with the addition of meal from the seeds of sesame, nut, and flax. It has been revealed that the indicators for elasticity, plasticity, and distensibility decrease compared to control sample by 4 % to 40 % when adding the meal of sesame, nut, and flax whose content ranges from 10 % to 30 %. Adding meals helps reduce the amount of gluten-free flour, which is a positive factor for making shortbread dough. Adding a composition of the specified meals at a ratio of 1.5:2:1.5 to shortbread dough increases the content of protein, fiber, macro- and micronutrients. We have performed sensory quality assessment of shortbread dough semi-finished products made from oil-seed meals. The distensibility of control and experimental samples of shortbread dough semi-finished products has been calculated when replacing flour with a 10 %, 20 %, and 30 % of the composition. We have estimated the structural-mechanical characteristics of shortbread dough – deformation, relative plasticity, elasticity, distensibility. A diagram has been constructed for the deformation dynamics of shortbread dough that contains the model compositions of sesame, nut, and flax meals. The developed dough semi-finished products demonstrate the reduced indicators for plasticity, elasticity, distensibility, and deformation. It has been determined that the amount of gluten in shortbread dough decreases and the developed products show a greater fragility. It was found that the best sensory indicators were demonstrated by the sample with a 20 % content of meals in the flour. We have experimentally confirmed the appropriateness of using oilseed meals, as well as devised a technology of flour confectionery products made from shortbread dough. It has demonstrated the increased protein content, by 2.4 times, selenium – by 41.2 times, fiber – by 4.7 times, calcium – by 18.4 times, magnesium – by 8.5 times, vitamin E – by 9.1 times. It was established that the developed functional products have improved food and biological value and fragility